OSU based M-OTN technology innovation and verification - Ruiquan JING; Xiaoli HUO; Junjie LI; Yi DING (Dianxin kexue)
As many carriers are stopping SDH/MSTP investment, OTN networks will replace SDH networks gradually and extend to the edge of the metro network, thus introducing new requirements for OTN technologies.In view of the challenges and new services requirements of the development of the metro optical transport network, the M-OTN technology with the optical service unit (OSU) as the core and optimized for the metro application was proposed.The progress of standardization and main contents of OSU technical standards were introduced, including OSU frame structure and overheads, OSU management frames, OSU hitless bandwidth adjustment mechanism.The consideration on M-OTN equipment types and existing network evolution strategy was given.The M-OTN prototype systems from mainstream manufacturers were tested.Test results show that OSU technology has significant advantages in latency, hitless bandwidth adjustment and transport efficiency.